THREE GIANTS – MEMBERS OF THE OPEN CLUSTER M 67 - Mishenina, T.; Klochkova, V.; Panchuk, V.; Basak, N.; Kovtyukh, V.; Korotin, S.; Velichko, A. (Одеські астрономічні публікації, 2017)
We determined the atmospheric parameters and chemical composition of the three giants, which are members of the open cluster M 67. The high resolution spectra (R = 60 000) were obtained with the echelle spectrograph NES mounted on the 6-metertelescope of the SAO RAS Obtained variations in Na and Zr abundances are within the determination errors. The Li abundance suggest a depletion of Li in the course ofstellar evolution. For studied giants, the iron abundances derived from the neutral and ionized iron lines have not shown any significant discrepancies. The [Ba/Fe] values are close to the solar ones.